2006
DOI: 10.1080/09663690601019794
|View full text |Cite
|
Sign up to set email alerts
|

Geographers Performing Nationalism and Hetero-masculinity

Abstract: Our article builds upon the insights of recent critical geographic inquiry that has examined the involvement of geography in a multitude of power relations, and in particular the processes of European imperialism and colonisation. The focus of this article, however, is the involvement of the discipline of geography in the constitution and maintenance of a hetero-masculine nationalist discourse. We focus our analysis on articles published in the New Zealand Geographer, but suggest that such hetero-masculine nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 40 publications
(36 reference statements)
0
15
0
Order By: Relevance
“…Benwell & Dodds, 2011;Coles, 2002;Henry & Berg, 2006;Jones & Merriman, 2009). Making independence meaningful is a process of performativity, that is, "the reiterative and citational practice by which discourse produces the effects that it names"; it is a "regulated process of repetition" (Butler, 1993, p. 2).…”
Section: The Performativity Of Independence Day In Finlandmentioning
confidence: 98%
See 1 more Smart Citation
“…Benwell & Dodds, 2011;Coles, 2002;Henry & Berg, 2006;Jones & Merriman, 2009). Making independence meaningful is a process of performativity, that is, "the reiterative and citational practice by which discourse produces the effects that it names"; it is a "regulated process of repetition" (Butler, 1993, p. 2).…”
Section: The Performativity Of Independence Day In Finlandmentioning
confidence: 98%
“…Dancing, bodily movement can be seen as a gendered social text and as such also supporting or threatening the existing socio-spatial order and moral conventions (Cresswell, 2006;Pine & Kuhlke, 2014). The dancing nation is assumed as being 'naturally' hetero-masculine (Henry & Berg, 2006). Former President Tarja Halonen's determination to promote social equity (Tiilikainen, 2010, p. 6) included the invitation of gay people to the party.…”
Section: Article In Pressmentioning
confidence: 99%
“…Feminist and cultural geographers have long highlighted the power of discourse in the construction, reproduction, and transformation of socio-political systems as it shapes both language and practice (Cock 1997;Henry and Berg 2006;Laclau 1994;Laclau and Mouffe 1985;Mueller 2008). To understand the construction and perpetuation of the state and military, one must consider discourse in terms of a performative, rather than simply descriptive, process.…”
Section: Fighting Words: Militarization Politics and Discoursementioning
confidence: 99%
“…On this score George Jobberns (1945, p. 5) succinctly concluded that the central purpose of the NZG was to ‘interpret our country to ourselves and to the outside world’. At the heart of the NZG then was a desire to embed the journal in the process of knowing the New Zealand nation, its peoples and its environments: a task framed both within the narratives of a masculinised, white‐settler society (Henry & Berg 2006) and an emerging consciousness of the environmental transformation wrought by that society (Pawson & Brooking 2002).…”
Section: A ‘Common Curiosity’mentioning
confidence: 99%
“…The quiet but profoundly performative role that geographical journals play in the production and dissemination of embedded ‘knowledge’ has been well documented (Berg 2009). Drawing on a performative vocabulary, we suggest that the journal did not simply reflect the practice of geographers in New Zealand but rather was utilised to discipline the discipline as a way of producing and stabilising a vision of geography framed by a set of intellectual and developmental relationships embedded in the wider context of a white‐settler society (Henry & Berg 2006). However, as we argue, this disciplining was not uncontested nor was it immutable.…”
mentioning
confidence: 99%